Genomic analysis of fibrolamellar hepatocellular carcinoma - Lei Xu; Florette K. Hazard; Anne‐Flore Zmoos; Nadine S. Jahchan; Hassan Chaı̈b; Phillip M. Garfin; Arun Rangaswami; M Snyder; Julien Sage (2014)
Pediatric tumors are relatively infrequent, but are often associated with significant lethality and lifelong morbidity. A major goal of pediatric cancer research has been to identify key drivers of tumorigenesis to eventually develop targeted therapies to enhance cure rate and minimize acute and long-term toxic effects. Here, we used genomic approaches to identify biomarkers and candidate drivers for fibrolamellar hepatocellular carcinoma (FL-HCC), a very rare subtype of pediatric liver cancer for which limited therapeutic options exist. In-depth genomic analyses of one tumor followed by immunohistochemistry validation on seven other tumors showed expression of neuroendocrine markers in FL-HCC. DNA and RNA sequencing data further showed that common cancer pathways are not visibly altered in FL-HCC but identified two novel structural variants, both resulting in fusion transcripts. The first, a 400 kb deletion, results in a DNAJB1-PRKCA fusion transcript, which leads to increased cAMP-dependent protein kinase (PKA) activity in the index tumor case and other FL-HCC cases compared with normal liver. This PKA fusion protein is oncogenic in HCC cells. The second gene fusion event, a translocation between the CLPTM1L and GLIS3 genes, generates a transcript whose product also promotes cancer phenotypes in HCC cell lines. These experiments further highlight the tumorigenic role of gene fusions in the etiology of pediatric solid tumors and identify both candidate biomarkers and possible therapeutic targets for this lethal pediatric disease.